Programmed death-ligand 1 expression in non-small cell lung carcinoma - mechanism of regulation, association with other markers, and therapeutic implication - Tancoš, V; Blichárová, A; Plank, L (Klinicka onkologie, 2022)
BACKGROUND: Immune checkpoint inhibitors (ICI) targeting the programmed cell death protein 1 (PD-1) signaling pathway have dramatically improved the clinical outcomes of oncological patients having advanced non-small cell lung carcinoma (NSCLC). The immunohistochemical analysis of programmed death-ligand 1 (PD-L1) expression remains the most widely used and clinically validated bio-marker predicting efficacy of ICI in NSCLC patients, but it represents in isolation an imperfect tool. The PD-1 axis is intricately coupled with numerous cellular and molecular factors within the tumor microenvironment (TME) of NSCLC. Cellular factors implicated in the regulation process of PD-L1 expression in NSCLC are related to the activity of tumor infiltrating lymphocytes and cancer associated fibroblasts. Intrinsic molecular factors which affect the level of PD-L1 expression are associated with the presence of oncogenic driver mutations in the Kirsten rat sarcoma viral oncogene homolog and epidermal growth factor receptor genes and to rearrangements in the anaplastic lymphoma kinase. Furthermore, activation of hypoxic signaling pathways and the transforming growth factor beta 1 axis can have an impact on the level of PD-L1 expression in NSCLC. A deeper understanding of the complex mechanisms regulating PD-L1 expression is necessary to tailor the treatment with ICI in patients with advanced NSCLC. PURPOSE: In this review, we present an overview of key factors underlying the regulation of PD-L1 expression within the TME of NSCLC, which are, and potentially can be, exploited to improve the outcomes of immunotherapy targeting the PD-1 axis.
Keywords: B7-H1 Antigen; Tumor Microenvironment; nádorové mikroprostředí; immune checkpoint inhibitors; antigeny CD274; tumour infiltrating lymphocytes; antigeny CD279; non-small cell lung carcinoma; nádory plic; programmed death-ligand 1; Programmed Cell Death 1 Receptor; hypoxia -inducible factor-1α; programmed cell death protein 1; nemalobuněčný karcinom plic; Humans; biologické markery; Carcinoma, Non-Small-Cell Lung; epithelial to mesenchymal transition; tumor infiltrating lymphocytes; Biomarkers; Lung Neoplasms; lidé